ANALISIS PERBEDAAN ABNORMAL RETURN DAN VOLUME PERDAGANGAN SAHAM PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA SEBELUM DAN SESUDAH PENGUMUMAN PEMILIHAN UMUM PRESIDEN DAN WAKIL PRESIDEN RI - Desak Putu Suciwati; Ni Nyoman Tri Wiandari (Sekolah Tinggi Ilmu Ekonomi AMM, 2016)
This study aimed to analyze the differences of abnormal return and trading volume activity on mining stocks list before and after the elections for president and vice president on July 22, 2014. The observations of the average of abnormal return and trading volume activity did by 3 days before and 3 days after events, which were analyzed using Paired Sample T-Test. The data in this study was obtained from the Indonesia Stock Exchange covering the daily closing stock prices, the index of mining stocks, daily stock trading volume, and the number of shares outstanding. Return expectations counted by market-adjusted model. The sample that used are stocks wich included in the sector of mining in Indonesia Stock Exchange. Based on the results of the study, the average of abnormal return shows any significant difference obtained by investors that showed there are good news in the announcement of the presidential election events and vice president in 2014. Then the average of Trading Volume Activity (TVA) showed there is not significant difference between before and after the event that indicating the election of the president and vice president do not contain material information that causes significant fluctuations